Black Bodies on the Ground II: Examining Impactful Policing Policies and Analysis of Policing Disparities Affecting Unarmed African American Men (2015-2020) - Robinson, M. A. (Victims & offenders, 2024)
This article critically analyzed impactful policies and practices governing the policing of Black men historically, and investigated the role these policies played in contributing to the untimely deaths of unarmed Black men by police. The researchers examined cases of police-involved shootings as reported by the Washington Post, with a particular focus on the killing of unarmed Black men over a six-year time frame. It was found that unarmed Black men were disproportionately killed by police and this finding is consistent with prior research that has considered long-term trends in the occurrence of police killings based on race. The researchers conclude with policy recommendations at the local, state, and federal levels to help stem the crisis.